An Investigative Preparation of Unfired Bricks from Clay and Fine Sand in the Presence of Sodium Hydroxide as an Activator through Geo-polymerization - Shetty, Hithesh Prabhakara; Shetty, Rakshith; Srinivasa, Shishir Golikoppa; Vishwanath, Sumanth Achira; Sharma, Subrahmanya Ramachandra; Saralaya, Sanjay Sukumar (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2024)
The present work was focused on an alternative method for the preparation of clay bricks by the mediation of sodium hydroxide solution as an efficient activator. The traditional brick preparation requires a firing process, but the present innovation avoids it by the use of commercially viable alkali as an activator. Various brick specimens were prepared by the addition of sodium hydroxide solution having different molarities to clay samples. This was done to optimize the process and contribute to process cost reduction. The blends obtained were molded as per the standard brick dimension (19X9X9 cm) and exposed to the ambient atmosphere in a well-ventilated room for curing (14-28 days). The clay samples and the brick specimens were subjected to some critical qualitative tests. Based on the results it was established that increasing the alkali addition to clay had gradually reduced the brick quality. Moreover, the inclusion of fine sand in the blend enhanced the brick quality. In this work, we emphasized optimizing the alkali input, the impact of reduced curing duration, avoiding brick firing, and the fine sand impact on the brick quality.